It's not me! It's him! Interactive puppet play to help children cope. (1st July 2020) - Linn, Susan
Puppetry has been described as one of the most valuable and least understood of all tools for play therapy. This article describes the author's experience using puppets to help children facing serious illness and hospitalization. One lens for understanding why puppetry is such a powerful therapeutic tool is informed by psychodynamic theory, especially object relations, in particular D. W. Winnicott's writings on play, as well as the seminal work of Anna Freud and Melanie Klein in describing the psychological phenomena of projection and identification. In this context, the article explores, and gives examples of, the characteristics of therapeutic puppet play that facilitate mastery, modelling and self-expression.